Perancangan Komik Strip Untuk Menghadapi Patah Hati Karena Putus Cinta Di Kalang Remaja - Afdalia Nur Syafitri; Rina Nurfitri (LPPM STIKI Malang, 2023)
This study aims to make comics as entertainment when teenagers experience heartbreak due to a breakup. The application chosen as the publication media is Line Webtoon. The comics that are made are comic strips. The research method used in this research is descriptive procedural with a systematic design consisting of define, research, ideate, prototype, select, implement, and learn. Making comics is also assisted by several digital tools, Paint tool SAI, for the image process to coloring, while for making word balloons using the Corel draw application. Data analysis techniques in this study were interviews and questionnaires of 38 people. The results of interviews with psychologists as well as readers explain that comics have a positive impact as entertainment and reduce the impact experienced by teenagers when they are heartbroken and can effectively be used as a coping mechanism to reduce feelings of sadness when they experience broken heart.